Data from lake cores from lakes in northern Seward Peninsula, Alaska (Arctic Data Center)
In 2009 and 2010, we extracted sediment cores from seven key study lakes on the NW Seward Peninsula. Various physical, chemical and biological properties were measured including grain size, magnetic susceptibility, macrofossils, %TOC, del13C, del15N, % biogenic silica, grain size, and composition using smear slides.